Cybersecurity in Telemedicine: A Technical Implementation Guide - Smita Verma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid evolution of telemedicine has fundamentally transformed healthcare delivery while introducing complex cybersecurity challenges. This comprehensive article examines critical security components, third-party risk management, compliance frameworks, and incident response strategies in virtual healthcare environments. The article explores encryption implementations, authentication mechanisms, and secure communication architectures essential for protecting patient data. It addresses HIPAA technical safeguards, security training protocols, and platform architecture considerations while highlighting the importance of continuous security testing and monitoring. The article emphasizes the need for healthcare organizations to balance operational efficiency with robust security measures, focusing on automated threat detection, forensic capabilities, and recovery protocols to maintain the integrity and confidentiality of healthcare systems.
Keywords: Telemedicine Cybersecurity; Healthcare Data Protection; HIPAA Compliance; Incident Response Framework; Security Training Protocol